Malnutrition, hypertension risk, and correlates: An analysis of the 2014 Ghana Demographic and Health Survey data for 15–19 years adolescent boys and girls - Azupogo, Fusta; Abizari, Abdul-Razak; Aurino, Elisabetta; Gelli, Aulo; Osendarp, Saskia J. M. (MDPI, 2020)
The sex differences in malnutrition and hypertension during adolescence is largely inconclusive. There is also a paucity of data on the sex-specific correlates of malnutrition and hypertension for adolescents. Hence, this study aimed to assess the association between malnutrition, pre-hypertension/hypertension (PHH) and sex among adolescents. The study also aimed to determine and contrast the factors associated with these risks in Ghana. We analysed data of non-pregnant adolescent girls (n = 857) and adolescent boys (n = 870) aged 15–19 years from the 2014 Ghana Demographic and Health Survey (DHS). We modelled the prevalence risk ratio (PRR) of malnutrition and PHH using Cox proportional hazard models. Compared to adolescent girls, boys were more than twice likely to be stunted (PRR = 2.58, 95% C.I (1.77, 3.76)) and underweight (PRR = 2.67, 95% C.I (1.41, 5.09)) but less likely to be overweight/obese (PRR = 0.85, 95% C.I (0.08, 0.29)). Boys were also about twice likely to have PHH (PRR = 1.96, 95% C.I (1.47, 2.59)) compared to their female peers. Girls were more at risk of the detrimental effects of poor education on stunting and PHH. Empowerment index while protective of stunting for girls (PRR = 0.82, 95% C.I (0.67, 0.99)) also increased their risk of overweight/obesity (PRR = 1.31, 95% C.I (1.02, 1.68)). A higher household wealth index (HWI) increased the risk of overweight/obesity for adolescent girls but was protective of stunting and PHH for adolescent boys. Improvement in household water, hygiene, and sanitation (WASH) reduced the risk of stunting by 15% for adolescent boys. Overall, our findings suggest a double-burden of malnutrition with an up-coming non-communicable disease burden for adolescents in Ghana. Our findings may also be highlighting the need to target adolescent boys alongside girls in nutrition and health intervention programmes.